The Relationship Between Job Demands and Job Resources and Teacher Burnout: A Systematic Literature Review - Rosinta, Widia; Kristanto, Agung; Solikhah, Solikhah (Reflection Journal, 2026)
This study aims to identify and synthesize empirical evidence on the relationship between job demands, job resources, and burnout in the teaching profession through a Systematic Literature Review (SLR) approach. The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and employed the PIOT framework (Population, Issue, Outcome, Type of Study) to formulate research questions and guide the search strategy. Literature searches were conducted in two electronic databases, Google Scholar and PubMed, covering publications from 2021 to 2025. Of the 602 articles initially identified, six studies met the inclusion criteria after systematic screening and full-text eligibility assessment and were subsequently analyzed in depth. The synthesis of findings indicates that job demands particularly workload, role conflict, and role ambiguity are consistently and positively associated with teacher burnout. In contrast, job resources such as social support and a supportive work environment tend to function as protective factors, although their buffering effects vary across educational contexts and organizational conditions. These findings underscore the complex and context-dependent nature of the relationships between job demands, job resources, and burnout. This review contributes theoretically by reinforcing the Job Demands–Resources framework within the context of the teaching profession and offers practical implications for policymakers and school administrators in developing more comprehensive and sustainable strategies to prevent teacher burnout